2013
DOI: 10.1148/radiol.13121606
|View full text |Cite
|
Sign up to set email alerts
|

Breast Ultrasonography: State of the Art

Abstract: Ultrasonography (US) is an indispensable tool in breast imaging and is complementary to both mammography and magnetic resonance (MR) imaging of the breast. Advances in US technology allow confident characterization of not only benign cysts but also benign and malignant solid masses. Knowledge and understanding of current and emerging US technology, along with the application of meticulous scanning technique, is imperative for image optimization and diagnosis. The ability to synthesize breast US findings with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
179
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(180 citation statements)
references
References 125 publications
0
179
0
1
Order By: Relevance
“…In addition to mammography, US has become a standard non-invasive diagnostic imaging method used for the detection of breast cancer, particularly in the dense breast [32][33][34]. Over the years breast US elastography has evolved as an adjunct to conventional US, becoming a valuable tool in clinical practice [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mammography, US has become a standard non-invasive diagnostic imaging method used for the detection of breast cancer, particularly in the dense breast [32][33][34]. Over the years breast US elastography has evolved as an adjunct to conventional US, becoming a valuable tool in clinical practice [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Lesions deeper than 2 cm are less accurately characterized by means of shear-wave elastography. 7 The latest edition of the BI-RADS ® atlas includes elastographic findings, and lesions are classified as soft, intermediate, or hard. This classification is based on the same principles that were suggested by the authors, in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…UE, as a novel ultrasound imaging technique based on the measurement of the relative hardness of a lesion against the adjacent normal tissues, has the ability to yield a more accurate estimation compared with conventional ultrasound examination technology in the differentiation of malignant from benign breast lesions (16). A previous study has demonstrated that UE was helpful in the differentiation of benign and malignant breast lesions since the hardness of malignant breast cancer was 2-3 times higher than that of benign cancer (17).…”
Section: Discussionmentioning
confidence: 99%